Availability of Binaural Cues for Pediatric Bilateral Cochlear Implant Recipients - Sheffield, Sterling W. (J Am Acad Audiol, 2015)
BACKGROUND: Bilateral implant recipients theoretically have access to binaural cues. Research in postlingually deafened adults with cochlear implants (CIs) indicates minimal evidence for true binaural hearing. Congenitally deafened children who experience spatial hearing with bilateral CIs, however, might perceive binaural cues in the CI signal differently. There is limited research examining binaural hearing in children with CIs, and the few published studies are limited by the use of unrealistic speech stimuli and background noise. PURPOSE: The purposes of this study were to (1) replicate our previous study of binaural hearing in postlingually deafened adults with AzBio sentences in prelingually deafened children with the pediatric version of the AzBio sentences, and (2) replicate previous studies of binaural hearing in children with CIs using more open-set sentences and more realistic background noise (i.e., multitalker babble). RESEARCH DESIGN: The study was a within-participant, repeated-measures design. STUDY SAMPLE: The study sample consisted of 14 children with bilateral CIs with at least 25 mo of listening experience. DATA COLLECTION AND ANALYSIS: Speech recognition was assessed using sentences presented in multitalker babble at a fixed signal-to-noise ratio. Test conditions included speech at 0° with noise presented at 0° (S(0)N(0)), on the side of the first CI (90° or 270°) (S(0)N(1stCI)), and on the side of the second CI (S(0)N(2ndCI)) as well as speech presented at 0° with noise presented semidiffusely from eight speakers at 45° intervals. Estimates of summation, head shadow, squelch, and spatial release from masking were calculated. RESULTS: Results of test conditions commonly reported in the literature (S(0)N(0), S(0)N(1stCI), S(0)N(2ndCI)) are consistent with results from previous research in adults and children with bilateral CIs, showing minimal summation and squelch but typical head shadow and spatial release from masking. However, bilateral benefit over the better CI with speech at 0° was much larger with semidiffuse noise. CONCLUSIONS: Congenitally deafened children with CIs have similar availability of binaural hearing cues to postlingually deafened adults with CIs within the same experimental design. It is possible that the use of realistic listening environments, such as semidiffuse background noise as in Experiment II, would reveal greater binaural hearing benefit for bilateral CI recipients. Future research is needed to determine whether (1) availability of binaural cues for children correlates with interaural time and level differences,(2) different listening environments are more sensitive to binaural hearing benefits, and (3) differences exist between pediatric bilateral recipients receiving implants in the same or sequential surgeries.